1986
DOI: 10.1079/bjn19860142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preweaning nutritional deprivation on basal metabolism and thermoregulatory thermogenesis in the rat

Abstract: 1. Nutritional deprivation was induced preweaning in Wistar rats by increasing the litter size to sixteen, while paired litters with only five pups served as controls. The nutritionally deprived pups were rehabilitated after weaning by ad lib. access to an adequate diet.2. The body-weights and body lengths were significantly lower in the nutritionally deprived group and significant differences persisted even after 9 weeks of rehabilitation.3. The body temperature of the nutritionally deprived animals was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Present data also show that long‐term changes in caloric intake affect the expression of UCP3 mRNA but not of UCP2 mRNA in skeletal muscle. An increased litter size, a well‐established model of nutritional deprivation before weaning [16], resulted in a reduced UCP3 mRNA expression. This behavior is similar to that found in adult rodents exposed to chronic caloric under‐nutrition [22] and contrasts with the up‐regulation of UCP3 mRNA due to fasting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Present data also show that long‐term changes in caloric intake affect the expression of UCP3 mRNA but not of UCP2 mRNA in skeletal muscle. An increased litter size, a well‐established model of nutritional deprivation before weaning [16], resulted in a reduced UCP3 mRNA expression. This behavior is similar to that found in adult rodents exposed to chronic caloric under‐nutrition [22] and contrasts with the up‐regulation of UCP3 mRNA due to fasting.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, UCP2 gene expression in skeletal muscle is developmentally regulated but this regulation is insensitive to nutritional changes. In some of the physiological and nutritional situations studied here, there is a correlation between thermogenic activity and UCP3 mRNA expression, as for example in the early postnatal period, when high thermogenesis occurs [23], or in nutritionally deprived pups, which show reduced non-shivering thermogenesis [16]. In these situations, fatty acids would play multiple roles in thermogenesis, they are the most calorigenic oxidation substrates, they promote mitochondrial uncoupling through UCPs and other mitochondrial anion carriers [5] and they regulate UCP3 mRNA synthesis in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it has been reported that food restriction imposed throughout the lactation period by increasing the number of pups per litter led the restricted animals to have lower rectal temperature than the controls, although cold-induced thermogenesis is present. These data suggest a possible impairment in the hypothalamic set-point as a consequence of food restriction imposed during the lactation period [18][19][20].…”
Section: Introductionmentioning
confidence: 99%